Guide to load analysis for durability in vehicle engineering - Johannesson, Par.; Speckert, Michael.; Dressler, Klaus. (Automotive series ;, 2014)
"Covers the use of established computational methods, such as finite element method (FEM) and multi body simulation (MBS), and their appropriate use within load analysis for durability"--